Performance of industrial dough mixers and its effects on noodle quality - Rui, Liu; Yimin, Wei; Yangyang, Lu; Yanan, Xing; Yingquan, Zhang (International Journal of Agricultural and Biological Engineering, 2016)
The effects of different types of industrialized dough mixing units on the characteristics of noodle dough and noodle quality were investigated. The study involved four mixing units, including two horizontal mixers with double shafts and two continuous high-speed mixers. Of the four mixing modes, mixing mode I, which used a horizontal pin-mixer with a constant mixing speed, provided the worst performance. This finding was indicated by worse mixing uniformity and noodle quality, larger-sized dough crumbs, lower hardness and chewiness of cooked noodles, and lower sensory scores of both color and elasticity. Mixing mode II, which used a horizontal mixer with angled, large surface-area blades and adjustable-speed mixing, gave the best performance. The flour hydration was observed to be even, and smaller even-sized dough crumbs were formed. During boiling of the dried noodles, there was lower water uptake, less cooking loss, and the cooked noodles showed better stickiness scores with higher hardness and chewiness of TPA compared to the other mixing modes. Mixing mode III involved a vertical continuous high-speed mixer with a speed of 970 r/min and had better mixing uniformity compared to mixing mode IV, which involved a horizontal high-speed mixer and a higher mixing speed of 1440 r/min. No single mixer performed best over all three flours. Therefore, the final choice of mixing modes should be based on the major flour type used by the noodle manufacturer.Keywords: industrial dough mixers, mixing speed, mixing performance, noodle qualityDOI: 10.3965/j.ijabe.20160901.1448Citation: Liu R, Wei Y M, Lu Y Y, Xing Y N, Zhang Y Q. Performance of industrial dough mixers and its effects on noodle quality. Int J Agric & Biol Eng, 2016; 9(1): 125-134.